2015
DOI: 10.1111/sed.12196
|View full text |Cite
|
Sign up to set email alerts
|

Forced regressive deposits of a deglaciation sequence: Example from the Late Quaternary succession in the Lake Saint‐Jean basin (Québec, Canada)

Abstract: International audienceDifferentiating between forced regressive deposits from deglacial periods inhigh latitude domains and forced regressive deposits from the onset of glacialperiods in low latitude domains is fundamental for the accurate interpretationof glacial cycles within the geological record and then for thereconstruction of palaeogeography and palaeo-climate. A forced regressivedeglacial sequence is documented from the Lake Saint-Jean basin (Quebec,Canada). In this area, the Late Pleistocene to Holoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 92 publications
(134 reference statements)
1
24
0
Order By: Relevance
“…The boundary underlying the swash laminated sands is also a 1 st order surface (Fig.4), because it represents another beginning of a storm deposition. The record of 2 nd order surfaces is uncommon, due to the fact that washover deposits are often eroded by subsequent storms as identifi ed in Fig.2c and suggested by Nutz, especially in forced regression conditions (Nutz et al, 2015). The 3 rd order surfaces described in this study are comparable to the 1 st order and 2 nd order surfaces defi ned by Miall (1996), representing sedimentation of similar bedform type.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The boundary underlying the swash laminated sands is also a 1 st order surface (Fig.4), because it represents another beginning of a storm deposition. The record of 2 nd order surfaces is uncommon, due to the fact that washover deposits are often eroded by subsequent storms as identifi ed in Fig.2c and suggested by Nutz, especially in forced regression conditions (Nutz et al, 2015). The 3 rd order surfaces described in this study are comparable to the 1 st order and 2 nd order surfaces defi ned by Miall (1996), representing sedimentation of similar bedform type.…”
Section: Discussionmentioning
confidence: 75%
“…The architecture records in the GPR and trenches shows the growth of this spit and washover features. Washover bounding surfaces similar to those described in this study have been described previously (Schwartz, 1982;Neal et al, 2003;Switzer et al, 2006;Switzer and Jones, 2008;Nebel et al, 2011;Nutz et al, 2015;Shan et al, 2015), although in those researches, no hierarchy model was proposed.…”
Section: Discussionmentioning
confidence: 80%
“…9). As a matter of fact, studies that tackled deglaciation sedimentary successions in the Quaternary have indeed demonstrated that proglacial deltaic systems may lack any evidence directly diagnostic of glacial processes, despite being fed by meltwater and glaciogenic sediments from retreating ice sheet margins (Nutz et al 2015;Dietrich et al 2017Dietrich et al , 2018. In the current case study, the presence of laminated fine-grained sediments (FA2) suggest the influence of a seasonal climatic setting and as such may represent varvites (i.e., alternation between cold and warmer seasons; Zolitschka et al 2015) in periglacial lakes (Catuneanu et al 2005) although the annual character is not demonstrable here.…”
Section: Paleoenvironmental Reconstruction: No Direct Evidence For Glmentioning
confidence: 99%
“…Consequently, F4-F7 facies are classified using the terminology proposed by Arenas-Abad, Vazquez-Urbez, Pardo-Tirapu, and Sancho-Marcéen (2010) which describes tufa in either lake shore or fluvial domains. The third type of sedimentary facies includes sandstones and conglomerates (F8-F11) reflecting deposition from mostly dilute flows attributed to the activity of a river system (Miall, 2014;Nutz et al, 2015;Schomacker, Kjemperud, Nystuen, & Jahren, 2010). All these sedimentary facies (Table 1) point to the existence of ancient lacustrine-to-fluvial sedimentary systems and document depositional environments such as offshore lake, lake margin, lake shore, fluvial cascade, alluvial plain and alluvial fan.…”
Section: Facies Description and Interpretationmentioning
confidence: 99%